THE INFLUENCE OF INTERNAL AND EXTERNAL FACTORS AS AN EXPLANATION OF CHANGES IN NON-PERFORMING FINANCING AT BANK BNI SYARIAH - Sudirman Sudirman; Trimulato Trimulato; Andi Sadapotto; Yulianti Yulianti (Tasharruf: Journal Economics and Business of Islam, 2022)
The purpose of this research is to analyze the influence of internal variables including Financing to Deposit Ratio (FDR), Capital Adequacy Ratio (CAR), Operational Costs to Operating Income (BOPO), and external variables, including Inflation and value of the exchange rate on Non-Performing Financing (NPF). The data used is secondary data obtained from financial statements from Bank BNI Syariah and Central Statistics Agency. The type of data analyzed is time series quarter period last ten years, from 2011 to 2020. The data analysis method is carried out using multiple regression with SPSS version 26. The results of this study found together the Financing to Deposit Ratio variables (FDR), Capital Adequacy Ratio (CAR), Operating Costs to Operating Income (BOPO), Inflation, and Exchange Rates have a significant effect on Non-Performing Financing (NPF). Meanwhile, the partial Financing to Deposit Ratio (FDR) variable has a negative and insignificant effect on Non-Performing Financing (NPF). Likewise, Operational Costs on Operating Income (BOPO) have a positive and insignificant effect on Non-Performing Financing (NPF). Meanwhile, Capital Adequacy Ratio (CAR) and Inflation have a positive and significant effect on Non-Performing Financing (NPF). However, the exchange rate has a negative and significant effect on Non-Performing Financing (NPF). The conclusions were tested together with variables Financing to Deposit Ratio (FDR), Capital Adequacy Ratio (CAR), Operating Costs to Operating Income (BOPO), Inflation, and Exchange rates have a significant effect on Non-Performing Financing (NPF) at Bank BNI Syariah.